Le management des « différences culturelles ». Circulation de l’essentialisme racial dans les multinationales en France - Anne Zhou-Thalamy (La Nouvelle Revue du Travail)
This article examines “intercultural management” in multinational corporations in France and the effects of these racial classifications on the discourses and practices of managers within the workplace. Within the context of the French ideal of colorblindness, how are cultural differences constructed and appropriated within these spaces? What are the effects of this racial framework? By focusing on the management of “Asian cultures”, this article explores the construction of cultural differences within multinational workspaces. Subsequently, it elaborates on the social characteristics of the consultants involved in the making and diffusion of this racial framework. Finally, the third part will examine the reception and use of these cultural management norms by actors at the top of the managerial hierarchy.